Informação e Inclusão acadêmica: um estudo sobre as necessidades socioinformacionais dos universitários cegos do Campus I da UFPB - Silva, Aparecida Maria da (2012)
The present paper aims to elucidate the informational actions used for the attendance of the social and informational needs of blind students at Campus 1 of the Federal University of Paraíba, identifying their informational needs and barriers more pertinent in the search and use of information. The methodology used Bardin s Analysis, by means of the categorization process based on Sense Making model of Brenda Dervin which, by means of meaning construction, intends to apprehend how users make sense through a subjective perspective. The obtained results revealed that there are some barriers, among them, informational, attitudinal and technical ones. Also, these barriers are not only for the blind student, but also among professors, in relation to the inclusive process, and the own University in the role of manager of possibilities, because it does not enable the usability of assistive technologies as a factor of digital inclusion in the entire educational context. The conclusion is that there is lack of pedagogical (in)formation of professors to change their social and educative praxis, as well as it suggests the realization of new researches about this problematic which reflects in the formation of professors and in the noiseless positioning of universities in relation to people with special needs.